Analysis of the Effect of Working Capital, Liquidity, Solvency, and Activity on Profitability in Pharmaceutical Sector Companies Listed on the Indonesian Stock Exchange - Alqoria Nur Azizah; Zulfa Irawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the impact of working capital, liquidity, solvency, and activity on profitability, with a specific focus on pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023—a sector chosen due to its distinctive financial dynamics, including high research and development expenditures, prolonged product cycles, and heightened relevance in the post-pandemic period. Utilizing a quantitative approach with panel data regression, the study incorporates model selection tests (Chow, Hausman, and Lagrange Multiplier) and classical assumption tests to validate the model, addressing potential issues such as multicollinearity, heteroscedasticity, and autocorrelation. The analysis is based on secondary data from a defined sample of pharmaceutical firms, with operationalization of variables such as “activity” measured through asset turnover ratios. Findings reveal that while liquidity exerts a significant positive influence on profitability, suggesting the importance of effective cash management and short-term asset optimization, working capital and solvency display negative yet statistically insignificant effects, possibly reflecting the sector's dependence on long-term investments and leveraged capital structures. The study underscores the need for pharmaceutical firms to balance liquidity with strategic allocation of capital in light of industry-specific constraints.